A new MIS 3 radiocarbon chronology for Mochena Borago Rockshelter, SW Ethiopia: Implications for the interpretation of Late Pleistocene chronostratigraphy and human behavior. (February 2017) - Brandt, Steven; Hildebrand, Elisabeth; Vogelsang, Ralf; Wolfhagen, Jesse; Wang, Hong
Abstract: With excavated layers spanning a period from > 49 ka to ~ 36 ka, Mochena Borago Rockshelter reveals a complex sequence of Late Pleistocene human occupation punctuated by volcanic events. Fifty-nine radiocarbon ages make Mochena Borago one of the best-dated Late Pleistocene archaeological sites in eastern and northeastern Africa. However, complex site formation processes, dramatic stratigraphic differences between non-contiguous excavation areas, and "outlier" dates that appear in various parts of Mochena Borago's sequence, complicate efforts to develop a secure and detailed chronology for local and regional behavioral changes. This article focuses on contiguous squares within the Block Excavation Area (BXA) trench at the northern end of the shelter. Bayesian modeling of thirty-seven dates from six major lithostratigraphic units within the BXA yields a revised series of age ranges; these differ from the previous age model (derived from weighted means) in subtle but important ways. Perspectives gained through Bayesian analysis stimulate more careful consideration of the complex site formation processes operating at Mochena Borago, the contextual integrity of the site's robust and distinctive flaked stone artifact assemblages (lithics), and potential correlations between lithic changes and environmental events that occur on local, regional, and global scales. As these factors come into focus, Mochena Borago can serve as an important chronological benchmark to better understand human behavior in eastern and northeastern Africa around the time of the second major dispersal of Homo sapiens . Highlights: Dates are presented for MIS 3 archaeological deposits at Mochena Borago, SW Ethiopia. Bayesian modeling generates age ranges for six major lithostratigraphic groups. Within this chronological framework, changes in lithic technology are examined.